STUDI KOMPARATIF MENGENAI ALAT BUKTI SURAT DALAM HUKUM ACARA PERDATA INDONESIA DENGAN HUKUM ACARA PERDATA ISLAM - Muhammad Iqbal Tarigan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
The mix can be seen in the civil procedure law in Indonesia. Civil procedure law applicable in the District Court also applies to the Religious Courts. That is, the two judiciary institutions both refer to colonial law. The mixing of the civil procedure law clearly shows that both the district court and the religious court both recognize the letter of evidence as a tool that has perfect verification power. Where as if it is seen in Islamic civil procedural law then it is not a letter that has perfect power but an acknowledgment or pledge Keywords: Letter Evidence, Indonesian civil procedural law and Islamic civil procedure law